Pengaruh Reward Dan Efisiensi Kerja Terhadap Kinerja Karyawan PT. Hanjaya Mandala Sampoerna Tbk Sukorejo – Pasuruan - Anggre Maulidyatur Rohma; Nurhidayah Nurhidayah; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In this study, the aim is to determine the influence of reward and work performance on the job performance of PT employees. HM. Sampoerna Tbk. Sukorejo - Pasuruan. This study has a population of 850 employees. The sampling technique uses a purposive sampling method with 90 employees. Then, this study used questionnaires and interviews to collect data. To analyze the data itself, this study uses simple regression analysis. The results of this study explain that rewards and job performance have a positive impact on employee performance. Therefore, it can be said that the higher the reward and work efficiency, the better the performance of the employee. Reward and performance have a positive effect on employee performance. A fairer remuneration system will motivate employees to be more enthusiastic about taking control of their work, for example with the availability of compensation, benefits, career development and on-the-job training. work with quality, according to plan, efficiently.  Keywords: reward, work efficiency, employee performance